Parental Sex and Not Kinship Determines Egg Cannibalism in Arma custos Fallou (Hemiptera: Pentatomidae: Asopinae) - Wu, Shaolong; Zeng, Weiai; Deng, Wan; Li, Jiaying; Li, Mi; Tan, Lin; Cai, Hailin; Li, Xiaohong; Li, Youzhi; Zhou, Zhicheng (Frontiers in Ecology and Evolution, 2022)
Background: Arma custos Fallou (Hemiptera: Pentatomidae: Asopinae) is an important cannibalistic, predatory insect species native to China, Korea, and Mongolia. It is important to understand the evolution of egg cannibalism in A. custos to evaluate the biocontrol potential of this species. However, few reports have suggested egg cannibalism in A. custos, and whether hungry adult A. custos males and females prey on their eggs remains unknown. Here, we investigated the effects of the sex of A. custos adults on egg cannibalism of parental and non-parental eggs under no-choice and free-choice conditions, along with the effects of predator and egg density on egg cannibalism under starvation conditions. Results: We observed that females frequently visited and cannibalized a higher proportion of eggs, whereas males almost did not participate in egg cannibalism, less than 17% males showed egg cannibalism behavior. Moreover, regardless of their relationship with the egg, neither male nor female adults consumed all the available eggs even in the absence of an alternative food source and > 70% of eggs remained unconsumed. In contrast, cannibalistic males and females did not discriminate between parental and non-parental egg types. Additionally, the lifespan of A. custos adult females increased significantly with the increasing number of consumed eggs (P < 0.05). Conclusions: These findings suggest that A. custos adults display limited egg cannibalism, ensuring a continuous supply of insects for rearing that does not affect its biocontrol efficacy. Therefore, A. custos may be effectively used as a biocontrol agent.